UJI KEMAMPUAN ANTAGONISME KHAMIR ASAL DAUN JATI (Tectona grandis) TERHADAP KAPANG PENGKONTAMINAN PADA PAKAN TERNAK AYAM: Antagonism Ability Test Yeast Origin Teak Leaves (Tectona grandis) Against Mold Contaminator In Chicken Feed - Marham, Hilma Dianti; Rustam, Yoswita; Sukmawati, Dalia (LPPM Universitas Negeri Jakarta, 2016)
Antagonism is the interaction that occurs when a microorganism interfere with the growth of other microorganisms. One of the microorganisms that have antagonistic ability is yeast. The research aims to determine the ability of antagonism yeast derived from the leaves of teak (Tectona grandis) as an agent for controling mold from poultry feed is Aspergillus sp., Fusarium sp., and Penicillium sp. Tests carried out using the method of antagonism co-culture in medium Potato Dextrose Broth (PDB) during the four days of incubation temperature of 27-28Â°C. The results showed that yeasts have antagonism activity against Aspergillus sp., Fusarium sp., and Penicillium sp. shown by mycelial growth inhibition and sporulation. Co-culture method results obtained 5 potential yeast isolates (T3D2 DU 1.7, T4D2 WU2J2, T4D2 DU 2.1, T4D1 DU 2.1, T5D1 DU 2.2).